Subglacial bed form morphology controlled by ice speed and sediment thickness - Barchyn, Thomas E.; Dowling, Thomas P F; Stokes, Chris R.; Hugenholtz, Chris H. (Geophysical Research Letters, 2016)
Subglacial bed forms (drumlins, ribbed moraines, and megascale glacial lineations) are enigmatic repetitive flow-parallel and flow-transverse landforms common in glaciated landscapes. Their evolution and morphology are a potentially powerful constraint for ice sheet modeling, but there is little consensus on bed form dynamics or formative mechanisms. Here we explore shallow sediment bed form dynamics via a simple model that iterates (i) down-flow till flux, (ii) pressure gradient-driven till flux, and (iii) entrainment and deposition of sediment. Under various boundary conditions, replicas of subglacial bed forms readily emerge. Bed form dynamics mirror those in subaqueous and aeolian domains. Transitions between ribbed moraines and elongate flow-parallel bed forms are associated with increasing ice speeds and declining sediment thickness. These simulations provide quantitative flux estimates and suggest that widely observed transitions in shallow sediment subglacial bed forms (e.g., ribbed moraines to drumlinoids to megascale glacial lineations) are manifestations of subtle variations in ice velocity and sediment thickness.